2009
DOI: 10.2337/dc08-1223
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Prognosis of Diabetic Patients With Critical Limb Ischemia

Abstract: OBJECTIVE -To evaluate the long-term prognosis of critical limb ischemia (CLI) in diabetic patients. CONCLUSIONS -Diabetic patients with CLI have high risks of amputation and death. In a dedicated diabetic foot center, the major amputation, ulcer recurrence, and major contralateral limb amputation rates were low. Coronary artery disease (CAD) is the leading cause of death, and in patients with CAD history the impaired ejection fraction is the major independent prognostic factor. RESEARCH DESIGN AND METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
151
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(175 citation statements)
references
References 26 publications
14
151
0
7
Order By: Relevance
“…ABI <0.9 approximately doubles the risk of mortality and the risk is four-fold higher in patients with ABI values <0.6 [Ankle Brachial Index Collaboration, 2008]. The highest mortality rates were reported in patients in whom revascularization was not possible [Faglia et al 2009]. MAC is indicative of excess cardiovascular mortality [Allison et al 2008].…”
Section: Discussionmentioning
confidence: 99%
“…ABI <0.9 approximately doubles the risk of mortality and the risk is four-fold higher in patients with ABI values <0.6 [Ankle Brachial Index Collaboration, 2008]. The highest mortality rates were reported in patients in whom revascularization was not possible [Faglia et al 2009]. MAC is indicative of excess cardiovascular mortality [Allison et al 2008].…”
Section: Discussionmentioning
confidence: 99%
“…end points of minor amputation and healing because vessel patency alone is considered necessary but not sufficient to guarantee amputation-free survival. 2,8,21 However, post hoc analysis revealed that DEBs are likely to provide significant improvement in the rate of complete index ulcer healing at 12 months. The possibility that treatment with DEB might result in significant clinical benefit is further compounded by the more favorable distribution of Rutherford classes at follow-up and faster index ulcer healing in the DEB group.…”
Section: Discussionmentioning
confidence: 99%
“…Most amputations are carried out on people with diabetes mellitus, who have rampant atherosclerosis and poor angiomyogenesis (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%